Construction and Practice of the Whole Management Model of Breast Cancer Chemotherapy Outpatient Clinic Based on Doctor-nurse Integration Mode - GUO Hailing; ZHANG Jiahua; ZHANG Fan; LONG Yifang; WANG Changjun (Xiehe Yixue Zazhi)
ObjectiveTo explore the establishment, implementation, and outcomes of an integrated physician-nurse team-based comprehensive management model for breast cancer chemotherapy outpatients, aiming to provide a reference for standardized patient care.MethodsIn January 2019, the Breast Surgery Department of Peking Union Medical College Hospital developed an integrated physician-nurse team and established a full-cycle management pathway covering the pre-chemotherapy, chemotherapy, and inter-cycle phases. This model featured appointment-based scheduling, time-segmented visits, and closed-loop patient management. Key performance indicators-including healthcare efficiency, chemotherapy safety, staffing ratios, and satisfaction levels among patients and healthcare providers-were compared between pre-implementation(2018) and post-imple-mentation (2019) periods.ResultsBefore implementation, patient waited times ranged from 30 to 120 (75.40±20.97) minutes, with an annual chemotherapy volume of 8 715 cases. Two ward nurses were routinely redeployed daily to support the chemotherapy clinic. Post-implementation, patients received timely chemotherapy per scheduled appointments without delays, annual chemotherapy volume increased to 10 101 cases, and staffing between two chemotherapy units became flexibly adjustable. Ward nurses transitioned from an on-call to a reserve role. Adverse events (chemotherapy-related, catheter-related, and nursing incidents) remained at 0, consistent with pre-implementation levels. Both patient and staff satisfaction scores significantly improved across all domains (all P < 0.05).ConclusionsThe integrated physician-nurse team-based chemotherapy management model enhances service efficiency, ensures treatment safety, optimizes workforce allocation, and improves satisfaction among patients and healthcare providers.